2015
DOI: 10.1007/s11127-015-0267-6
|View full text |Cite
|
Sign up to set email alerts
|

Political fractionalization and delay in fiscal stabilizations: a duration analysis

Abstract: This article employs a duration analysis approach to empirically investigate whether political fractionalization leads to delayed fiscal stabilizations. Using a broad sample of both developed and developing countries for the period 1975-2011, we consistently find strong evidence that political fractionalization is significantly associated with longer delays in stabilizing high deficits. In particular, political fractionalization has a greater impact on delays in periods of macroeconomic distress. We also show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…De Haan and Sturm (1994) confirmed these results, showing that the accumulation of debt in the 1980s is positively associated with the frequency of government change in the member countries of the European Community. Grier et al (2015) used a sample of 90 developed and developing countries over the period 1975-2011 and showed that political fragmentation delays fiscal stabilisation. Clemens et al (2016) also support this idea and suggested that the more fragmented a government is (with larger and more unstable coalitions), the more difficult it will be for it to respond to a fiscal crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…De Haan and Sturm (1994) confirmed these results, showing that the accumulation of debt in the 1980s is positively associated with the frequency of government change in the member countries of the European Community. Grier et al (2015) used a sample of 90 developed and developing countries over the period 1975-2011 and showed that political fragmentation delays fiscal stabilisation. Clemens et al (2016) also support this idea and suggested that the more fragmented a government is (with larger and more unstable coalitions), the more difficult it will be for it to respond to a fiscal crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…to Carrasco (2001), the variable (parcom) may be exogenous 9 and should have an effect on the endogenous variable (y * it ) only through the stability of the government (ps it ). Indeed, as Grier et al (2015) explain, unstable governments (fragmented by coalitions) exist only when political participation is competitive. These two variables are very likely to be statistically correlated.…”
Section: Endogeneity and Unobserved Individual Componentsmentioning
confidence: 99%
See 3 more Smart Citations